Threads of Abraham: Interfaith memory and sacred survival in Geraldine Brooks’ People of the Book - Saleh, Shoeb; Ismail, Sayed M; Elsayed Hassan, Eid Awad Abd; Abdullatif, Ali; Koka, Nisar Ahmad (Research Journal in Advanced Humanities, 2026)
Geraldine Brooks’s People of the Book is often introduced as a historical novel about the Sarajevo Haggadah, yet its deeper achievement lies in the way it turns a Jewish ritual manuscript into an Abrahamic archive of shared custody, injury, and repair. This article proposes the concept of interfaith memory to describe how Brooks’s fiction connects Judaism, Christianity, and Islam not by smoothing their differences into a sentimental theology of harmony, but by staging the material survival of a sacred object across scenes of exile, censorship, war, artistic borrowing, and bodily risk. The Sarajevo Haggadah, a Passover book associated with Jewish telling and transmission, becomes in the novel a witness to Christian persecution, Muslim protection, secular conservation, and the unstable intimacy of cultures that have often lived together without living peacefully. Reading the novel through cultural memory studies, book history, material religion, trauma theory, and historiographic metafiction, the article argues that Brooks reimagines sacred survival as an ethical practice rather than a miraculous fact. Hanna Heath’s forensic conservation, the reverse chronology of the manuscript’s imagined past, and the repeated intervention of marginal figures—women, converts, artisans, librarians, servants, and endangered strangers—together form a narrative in which religious interconnection is carried by hands before it is declared by doctrines. At the same time, the article evaluates the limits of Brooks’s rescue plot, especially its tendency to make coexistence legible through exceptional acts of goodness. The novel’s value, I argue, is strongest when it refuses grand reconciliation and lets the damaged book remain damaged: a fragile, stubborn, humanly handled reminder that Abrahamic kinship is never pure inheritance but an unfinished labor of preservation.